Charting the growth of brain-based learning in higher education instructional design - Rodríguez Dueñas, Juan Santiago; Vargas Sánchez, Ana Dolores; Boude Figueredo, Oscar; Almenarez Mendoza, Florina (Frontiers in Education, 2026)
This study aims to delineate the scientific literature and articulate the intellectual framework linking brain-based learning (BBL) with instructional design in higher education over the past decade (2013–2024). A scoping review was performed in accordance with the PRISMA-ScR and Joanna Briggs Institute (JBI) criteria. Bibliometric analysis was conducted on articles indexed in Scopus and Web of Science through performance analysis and scientific mapping, particularly utilizing author co-citation analysis (ACA) with VOSviewer. The performance analysis indicates a significant increase in interest in the field since 2020. The co-citation analysis, utilizing a stringent threshold of 14 citations, identified an intellectual core of five key authors, categorized into two primary groups. The primary cluster embodies the essential discourse on the critical and pedagogical utilization of neuroscience in education, whereas the secondary cluster emphasizes the application of these principles in curriculum development. Research on BBL and instructional design is an evolving domain centered on a fundamental discourse over the legitimacy and application of neuroeducation. Substantial deficiencies are recognized in the merging of classical cognitive psychology ideas with the establishment of a technological research frontier.